Peran Pengalaman Berwirausaha Dan Faktor Emosional Terhadap Niat Pengembangan Usaha Pada Kalangan Pengusaha Muda Di Kota Medan - Ovan Krisadelman Zebua; Hasyim .; Farel Akbar Aditya Saragih; Kevin Valensius Siahaan; Simon Herbeth Beekham Saragih (STIE AMKOP, 2025)
This study analyzes the role of entrepreneurial experience and emotional factors on business development intentions among young entrepreneurs in Medan, where a dynamic MSME ecosystem encourages young people to seek economic independence amid limited formal employment opportunities. Using a qualitative approach based on a literature review with a systematic review of 35 secondary sources (journal articles, books, and case studies from 2015–2025), this study integrates the Theory of Planned Behavior (TPB) framework to explore thematic patterns from narratives of experience and emotional dynamics. Key findings indicate that entrepreneurial experiences serve as a source of practical learning that shapes business intuition and resilience to failure, while emotional factors such as optimism and stress regulation mediate perceptions of behavioral control, thereby jointly strengthening entrepreneurial growth intention. The integration of these two factors results in higher psychological readiness for business expansion in the context of Medan. The implications of this research include recommendations for entrepreneurship training that combines practical experience and emotional intelligence reinforcement to improve the sustainability of MSMEs.